PERAN DEWAN PENGAWAS DAN GOOD CORPORATE GOVENANCE PADA KINERJA BANK PERKREDITAN RAKYAT - I Gst Ayu Eka Damayanthi; Ni K.Lely Ary (Jurnal Akuntansi Indonesia, 2018)
This research starts from the many problems that occur in Bank Perkreditan Rakyat (BPR). From 2014 to 2016 the number of BPRs closed or liquidated by the Financial Services Authority (OJK) in the Deposit Insurance Corporation (LPS) report there are 14 BPRs. Based on the background of the problem, this research will examine the role of supervisory board and GCG on the performance of BPR in Gianyar Regency. This research will be conducted in Gianyar Regency. The sample is the head of the BPR, the finance department and the supervisory board of the BPR. Research sample 34 BPR and respondents were 105 respondents. Data were collected by disseminating research questionnaires. Analysis technique using multiple regression method. The results of the Supervisory Board’s research did not affect the performance of BPR in Gianyar Regency while GCG had a positive effect on the performance of BPR In Gianyar Regency. The suggestion of this research is to add other supervisors such as commissioners, audit committees or independent auditors as one of the independent parties that may affect the performance of BPR.Keywords: Supervisory Board, CGC, BPR Performance